The content of legally understood category of the rule of law as functioning in the political system of the European Union - Potorski, Radosław (The Copernicus Journal of Political Studies, 2025)
At its current stage of development the European Union is not only an organization for economic cooperation but also a community built around clearly defined values. Due to their importance, part of these values take the form of categories enshrined in law, i.e. the legal rules of EU political system. Hence all the goals of the EU should be pursued in respect of these values and in compliance with their spirit. One of the crucial values in this group is the rule of law or the concept of legal state (Rechtstaat). Respect for it is a prerequisite for uniform compliance with all EU law, for uniform implementation of EU solutions, and thus for building the trust of all EU citizens and national bodies in the legal systems of other countries. And though it may seem that the rule of law should not be in any way controversial, even its content as included in EU regulations still can stimulate a heated discussion in some member states, and sometimes (like in Poland) becomes the subject of a political dispute. Considering its significance, it is hard to deny that a sound interpretation of the legal category of the rule of law in the EU is necessary. The above considerations motivated the author to posing a question: How has the definition of the rule of law in the EU been shaping, and in particular, is it homogenous as to the source type, or should it be reconstructed from a variety of sources? The research hypothesis states that the definition of the rule of law developed in several stages, so its reconstruction should be based on a set of sources created at different times and varying in terms of importance.